Job Satısfactıon Level of Nurses - Satıhanım Tilev; Kerime Derya Beydağ (Association of Nurse Managers, 2015)
OBJECTIVE: This study has been carried out as descriptive reseach with the object of determining the job satisfaction of nurses working at Çukurova Dr.Aşkım Tüfekçi Public Hospital. METHODS: In this study as a method of student-t test and ANOVA in comparison to more than two variables, normal distribution parameters and the Mann-Whitney U test to compare more than two variables in the Kruscal Wallis tests were used. Considering the findings of the study, nurses' job satisfaction was found to be X = 59.6 +17.0. RESULTS: Results of the study in the province of Adana Seyhan district health service providers Cukurova Dr. Askim Tüfekçi State Hospital nurse who served as gender, age group, marital status, educational levels significantly not associated (p> 0.05), a work where they work and working hours according to the variables were found to show a statistically significant relationship (p <0.05). CONCLUSION: As a result of this study, nurses' job satisfaction has increased at a moderate level.